Efektifitas Aplikasi Bone Box dalam Menentukan Jenis dan Ciri Gigi Geligi - Listrianah, Listrianah; Nugroho, Taufik Alvin; Noviadi, Pitri (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2024)
Human teeth have an important role in the body to process and destroy food. Interactive learning multimedia, which is a learning media that is a combination of various media that are assembled in an integrated and interactive manner to convey messages related to certain learning. The technology in the field of multimedia that is developing today is Augmented Reality. An example of Augmented Reality-based learning media in the field of dental health is the Bone Box. Bone Box can display virtually 3D and real time interactively about dental anatomy is one way to deliver information faster and be able to understand and learn human tooth anatomy in an easy and fun way. Method of this type of research is Quasi Experiment with the form of two group pre-test – post-test. Research sample amounted to 40 students who were divided into 2 groups treatment and control. Results of the T-Test test obtained (p0.05) where it can be said that there is a difference in intent seen from the average difference in student knowledge scores before and after learning using Bone Box media. The conclusion that Bone Box media is effective for knowledge about the types and characteristics of teeth in Palembang Dental Health Department students.